1999
DOI: 10.1177/070674379904400405
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Unfitness to Stand Trial: Psychological Analysis of a Legal Issue

Abstract: The structure of the legal concept of unfitness to stand trial and how it corresponds to psychometric concepts is examined. We conclude that psychometric attempts at quantification and measurement are logically flawed, because they inappropriately treat fitness/unfitness as an individual trait rather than as situation-specific conjunctive/disjunctive concepts. It is argued that, whereas psychometric approaches may be suitable for measuring single components of unfitness, an overall "fitness" score is meaningle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…That is, they can provide a framework within which evaluators may assess their clinical decision-making. Veiel and Coles (1999) suggested that although it may be appropriate to assess elements of competence psychometrically, a global or overall score on an AC measure is meaningless and logically flawed. They argued that a competence determination requires the simultaneous consideration of several different capabilities in the context of the specific demands of that defendant's legal situation.…”
Section: General Issues Related To Ac Assessmentmentioning
confidence: 99%
“…That is, they can provide a framework within which evaluators may assess their clinical decision-making. Veiel and Coles (1999) suggested that although it may be appropriate to assess elements of competence psychometrically, a global or overall score on an AC measure is meaningless and logically flawed. They argued that a competence determination requires the simultaneous consideration of several different capabilities in the context of the specific demands of that defendant's legal situation.…”
Section: General Issues Related To Ac Assessmentmentioning
confidence: 99%
“…Despite good overall agreement in terms of CST decision, per se, considerable divergence existed regarding the reasons for these decisions. Veiel and Coles (1999) operationalized the CST construct differently. They argue, quite reasonably, that fitness is a relative concept as it must be defined individually relative to the demands of a particular trial.…”
Section: Recent Psychological and Psychiatricmentioning
confidence: 99%
“…They comment on the lack of attention paid to the specific deficits of mentally retarded individuals in that they often learn to reply with stock answers to facilitate social interac-tions but have very little understanding of the concepts that they articulate. Veiel and Coles (1999) conclude that psychological measurement is inappropriate for CST and, at most, the roles for psychological instruments should be limited to construct explication and standardization and validation of procedures for component constructs. They favor a branched questioning model with each successful answer entailing a question designed to establish the limits of comprehension of the previous answer, proceeding to asymptote.…”
Section: Recent Psychological and Psychiatricmentioning
confidence: 99%
“…It draws liberally from the author's recent articles, particularly Veiel and Coles (1999), Coles and Grant (1999) and Coles (1999). Dr E. Michael Coles, PhD, RPsych, Department of Psychology, Simon Fraser University, Burnaby, BC, Canada …”
mentioning
confidence: 96%